Evaluasi Program Indonesia Pintar dalam Peningkatan Akses Pendidikan di Sekolah Menengah Pertama - Wirastiani Binti Yusup; Bambang Ismanto; Wasitohadi Wasitohadi (Universitas Kristen Satya Wacana, 2019)
This study aimed to evaluate the design, installation, process, product, and analysis of benefits and costs of the implementation of the Program Indonesia Pintar (PIP) in Improving Access to Education in SMP Negeri 7 Salatiga. This research type is evaluative research using Discrepancy Evaluation Model. Data collection techniques used interviews, observations and document studies. Data analysis through: data collection, data reduction, data display, and conclusion. Data validation uses source triangulation and technique. The research results: (1) design components are formulated with reference to PIP Juknis in 2015 covering aspects of objectives, processes, human resources, facilities and infrastructure, (2) installation components there is still discrepancy between PIP implementation objectives with PIP objectives in junior State 7 Salatiga, (3) process components, planned programs are running in accordance with PIP Permendikbud, although in the implementation there are inhibiting factors, (4) product components, the objectives achieved are learners can buy school purposes, paying school administration fees (5) benefit and cost analysis components, PIP funding benefits are great for underprivileged learners, although PIP funds are still very poor in meeting the educational needs of learners each year.